Espectro vibracional dos Complexos Tioglicolatos de ZN(II) e CD(II), e orbitais naturais de ligação - (:unkn) unknown (Universidade Brasil, 2022)
Thioglycolic acid (ATG) is considered as a scavenger of heavy metals present in water through the formation of different metal complexes, but little is known about the structure of the metal complexes formed by thioglycolic acid, as well as there are few studies concluded by spectroscopy vibration characterizing these complexes. The objective of this work was to characterize the vibrational spectrum of Zn(II) and Cd(II) thioglycolate complexes, as well as determine their structures, obtain the natural bond orbitals (NBO) by quantum mechanical procedures, and determine predictions of pharmokinetics in silica from the compounds. The thioglycolate complexes of Zn(II) and Cd(II) were synthesized using the graphical method, the structural analysis was performed by the theoretical-experimental method using the hybrid RHF/MP2:STO 3G regarding the experimental spectra with Fourier transform infrared and Raman (FT-IR, FT-Raman). The calculations were performed using the optimized geometric structure to obtain the harmonic vibrational wave numbers for both complexes obtained. The second derivative of vibrational spectra and band deconvolution analysis were also performed. The infrared and Raman spectra show many combination bands and overtones in both cases. The calculated and experimental spectra confirmed the structural hypothesis considering two ATG (thioglycolic acid) with two water molecules in the coordination sphere of the central atoms. Natural bonding orbital (NBO) analysis was also performed to study the hybridization of Zn(II) and Cd(II) resulting in a pseudo-octahedral geometry for both complexes. The calculated and experimental spectra confirmed the structural hypothesis considering two ATG (thioglycolic acid) with two water molecules in the coordination sphere of the central atoms.
Keywords: Complexos de tioglicolatos de Zn(II) e Cd(II); Espectro vibraciona; Análise dos orbitais naturais de ligação (NBO); Engenharia Biomédica (Bioengenharia)